Synthesis and biomedical applications of magnetic iron oxide nanoparticles MIONs: a brief review - Albert, Emmellie Laura; Norman, Ashreen; Mat Yaacob, Siti Nor Zulfikaini; Zainuri, Muhammad Zulfadzli; Che Abdullah, Che Azurahanim (Electroactive Materials Society, 2021)
Magnetic iron oxide nanoparticles (MIONs) with multifunctional properties have recently attracted significant attention from researchers, not only for their intrinsic scientific value, but also for the plethora of technological applications enabled by their wondrous properties. MIONs are defined by their dipole configuration in the absence and presence of an external magnetic field, and their applications are diverse, including electronic, environmental, and biomedical. MIONs are well-known for their superparamagnetic properties, small size, and broad range of applications. MIONs have been found to be biocompatible with the human system to a degree since haemoglobin's chelator is composed of Fe (II) atoms. MIONs with desirable properties and a wide variety of biomedical applications are highly sought after. MIONs have received widespread recognition for their countless applications in a variety of fields, including nanobiotechnology and biomedicine. Due to their superparamagnetic properties and small size, MIONs are widely used in a variety of fields. Thus, this review highlights and describes the research related to biomedical applications based on MIONs synthesised using various approaches. This semi systematic mini review summarises the work that has been done thus far on MIONs, beginning with an overview of the various methods used to fabricate MIONs, including physical, chemical, and biological methods. Due to the importance of the surface chemistry of MIONs in biomedical applications, this review focuses on several common synthesis methods and their associated used in biomedical applications are defined. This review will assist new researchers in selecting appropriate MIONs synthesis techniques and for their research interests. MIONs are discussed as a vehicle for targeted drug delivery, as well as their use in cancer treatment via hyperthermia. Other biomedical applications discussed in detail include magnetic resonance imaging and magnetic targeting.